Resgate de um rio urbano esquecido : promovendo a qualificação de uma cidade brasileira de médio porte - Morsch, Maiara Roberta Santos (2015)
This research presents an approach regarding the relationship between urban rivers and cities. This element, which was already highly valued as an essential resource for human settlements, began a process of degradation in the mid-nineteenth century. As the cities grew, various technologies were created and the rivers were forgotten. Treated as growth restrictors and a problem in the urban environment, the rivers became places of eviction and irregular housing. At present, much is discussed about ecology and sustainable development, more than a century has passed and urban rivers are in the same situation, especially in medium-sized cities. And it is in search of a new urban paradigm that this work brings a study in order to discuss the possibility of returning the rivers back to the social and ecological conviviality so that it is in harmony with the present city. This research aims to propose alternatives for the requalification of a forgotten urban river, through the implantation of green areas, starting from the case study of the Passo Fundo river in the city of Passo Fundo, Rio Grande do Sul. For its accomplishment a methodology is proposed divided into steps to meet the specific objectives proposed. In the first stage a survey of the existing data and the selection of a section of the river for the proposal were carried out. The physical aspects of the chosen area were investigated. In the third step an opinion questionnaire was applied to future prospective users. The research developed generated a conclusion about the study, showing the behavior of the river and the behavior of the city in relation to it in the course of its development. Thus, from the results obtained, one can analyze the data and, with the knowledge acquired in the case studies, define technical guidelines for intervention that aim to contribute to the Brazilian medium-sized cities, as well as specific criteria for the implementation of the intervention proposal in the place of study, demonstrating the feasibility of applying the guidelines developed. Thus, the contribution of the work is to generate recommendations for Passo Fundo that can also serve as an example for other cities that face the same problem with urban rivers.